A Population‐Based Correlation Analysis Between Hemoglobin A1c and Hemoglobin Levels - Tingyu Zhang; Tianyi Shi; Min Cao; Yunxi Ji; Yanbin Xue; Huayan Yao; Qiaomei Yin; Bin Cui; Zhen Xie; Ping He (Journal of Diabetes)
ABSTRACT Background Glycated hemoglobin (HbA1c) is widely used to assess long‐term glycemic control in individuals with diabetes. However, various conditions that affect hemoglobin levels or the lifespan of red blood cells can compromise the accuracy of HbA1c measurements. Despite extensive research, the relationship between HbA1c and hemoglobin remains unclear. This study aims to clarify this relationship by examining its correlation across diverse age and gender cohorts. Methods Data from 217,991 participants aged 20 to 69 years were collected from health examination centers in Southwest China. Standardized methodologies were used to measure HbA1c and hemoglobin levels. Generalized additive models (GAM) were utilized to analyze non‐linear relationships and adjust for potential confounding variables. Gender‐specific reference intervals (RIs) for hemoglobin were also established. Results A gender‐specific association was observed between HbA1c and hemoglobin levels. In men, HbA1c levels decreased with increasing hemoglobin. Among women, a negative correlation was observed in premenopausal women (aged ≤ 45 years), whereas postmenopausal women (aged > 45 years) showed a positive correlation, with HbA1c levels increasing as hemoglobin levels rose. Additionally, HbA1c levels increased with age in both genders, with a more pronounced rise in women after the age of 45. Conclusion This study highlights significant gender‐ and age‐related differences in the relationship between HbA1c and hemoglobin. The findings suggest that estrogen‐related metabolic changes may influence HbA1c levels, with potential implications for diabetes management and hormone therapy in postmenopausal women.